Should Diesel cars in Europe be discouraged? - Inge Mayeres; Stef Proost (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper examines the rationale for the different tax treatment of gasoline and diesel cars currently observed in Europe. First, we analyse possible justifications for a different tax treatment: pure tax revenue considerations, externality cons0iderations and constraints on the tax instruments used for cars and trucks. Next, an applied general equilibrium model is used to assess the welfare effects of revenue neutral changes in the vehicle and fuel taxes on diesel and gasoline cars. The model integrates the effects on tax revenue, environmental externalities, road congestion, accidents and income distribution.
Keywords: H2; H21; H23; R41; D58; 330; Transport policies; transport externalities; optimal taxation; marginal tax reform; gasoline and diesel; applied general equilibrium model; Mineralölsteuer; Dieselkraftstoff; Externer Effekt; Steuerwirkung; Allgemeines Gleichgewicht; Theorie; EU-Staaten